Predictors of self-care behaviors in patients with hypertension: The integrated model of theories of "planned behavior" and "protection motivation" - Farnaz Eslamimehr; Zahra Hosseini; Teamur Aghamolaei; Marzieh Nikparvar; Amin Ghanbarnejad (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Assessment of self-care behaviors in patients with hypertension may provide clinicians and practitioners with important information about how to better control hypertension. Therefore, the present study aimed to explore the predictors of self-care behaviors in patients with hypertension based on an integrated model of theories of planned behavior and protection motivation. MATERIALS AND METHODS: The present cross-sectional study was part of a larger study, conducted in 2022 on 344 hypertensive patients from Khamir County in Hormozgan Province in Iran. The sample was selected through a systematic random sampling. The patients completed a researcher-made questionnaire based on constructs of the theory of planned behavior and protection motivation theory. They also completed, Hypertension Self-Care Activity Level Effects (H-SCALE), Hypertension Knowledge-Level Scale (HK-LS), and a demographic questionnaire. The data were analyzed in SPSS 21 using the Pearson correlation coefficient, independent-samples T test, one-way ANOVA, and linear regression analysis. RESULTS: The participants' mean age was 47.34 ± 13.68 years. Adherence to medication, physical activity, weight management, diet, and nonsmoking scores were 42.7, 27.3, 66.3, 14.2, and 81.1, respectively. The linear regression model showed that behavioral beliefs (β = 0.366, P < 0.001), perceived rewards (β = −0.248, P < 0.001), control beliefs (β = 0.133, P = 0.013), and normative beliefs (β = 0.143, P = 0.025) were the major predictors of self-care behaviors in patients with hypertension. CONCLUSION: In light of the present findings, it can be concluded that it is crucial to change patients' attitudes toward self-care behaviors and improve the social acceptance of behavior and its development in society, and improve patients' control beliefs through goal-oriented education that develops resistance against the perceived rewards of the unfavorable behavior. Considering these constructs can act as strategies to promote self-care behaviors among patients.